Disparities in colonoscopy adherence and neoplasia detection after positive fecal immunochemical test: a retrospective matched cohort study - Stephanie Chaparro; Mostafa Eysha; Islam Hamza Zaki; Mona A. Ali; Hend A. Elsaka; Alejandro Robles; Marc J. Zuckerman; Sherif E. Elhanafi (Cancer Causes & Control, 2026)

Interaction of tectonic systems in the origin of monogenetic volcanism of the Ventura Volcanic Complex, Mexico - Randall Guevara-Betancourt; Luis Rodríguez-Sosa; Joselin Almaguer; Alfredo Aguillón-Robles; Vsevolod Yutsis; Damiano Sarocchi; Luis A. Rodríguez-Sedano; Oscar Guevara-Mansilla; Eduardo Gomez; Alejandro Sandoval; Margarito Tristán-González (Journal of South American Earth Sciences, 2026)

Microbial diversity and enzymatic potential for plastic degradation in contaminated dumpsites in Mazamitla, Jalisco - María Camila Sinisterra-Sierra; Amador Campos-Valdez; Alejandro Pereira-Santana; Jesús Alejandro Zamora-Briseño; Sandra L. Ramírez-Pérez; Jorge L. González-Escobar; Manuel R. Kirchmayr; Iliana Barrera-Martínez; Marcela Robles-Machuca; Leticia Casas-Godoy (Environmental Research, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Unravelling the paths to urban fruitfulness: factors behind insect pollination and reproductive success of a native tree - Giovana María Galfrascoli; María Silvina Fenoglio; Alejandro Enet; Gloria Robles; Ana Calviño (Urban Ecosystems, 2025)

Venom variation and ontogenetic changes in the Crotalus molossus complex: Insights into composition, activities, and antivenom neutralization - Miguel Borja; Gamaliel Castañeda-Gaytán; Alejandro Alagón; Jason L. Strickland; Christopher L. Parkinson; Areli Gutiérrez-Martínez; Bruno Rodriguez-López; Vanessa Zarzosa; Bruno Lomonte; Anthony J. Saviola; Julián Fernández; Cara F. Smith; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Marine Prosperity Areas: a framework for aligning ecological restoration and human well-being using area-based protections - Octavio Aburto-Oropeza; Valentina Platzgummer; Erica M. Ferrer; Catalina López-Sagástegui; Rocío de Guadalupe Abud Mirabent; América Ávalos Galindo; Fabio Favoretto; Alfredo Giron-Nava; Isabel Mendoza Camacho; Claudia Núñez Sañudo; Marisol Plascencia de La Cruz; Alejandro Robles (Frontiers in Marine Science, 2025)
Mechanisms for marine ecological protection and recovery, including area-based conservation tools like ‘Marine Protected Areas’ (MPAs) are necessary tools to reach the Aichi Target or the forthcoming 30x30 target set by the Kunming-Montreal Biodiversity Framework. However, full ecosystem recovery takes years to manifest and the idea that MPA protection alone will foster human well-being is frequently contradicted by socio-economic evidence. Therefore, a new framework for marine area-based conservation and ecosystem restoration that reconciles the discrepancies between ecological recovery and socio-economic growth timelines is needed to effectively meet global biodiversity conservation targets. We introduce the concept of ‘Marine Prosperity Areas,’ (MPpA) an area-based conservation tool that prioritizes human prosperity as opposed to passively relying on ecosystem recovery to catalyze social change and economic growth. This concept leverages a suite of tried-and-true community-based intervention and investment strategies to strengthen and expand access to environmental science, social goods and services, and the financial perks of the blue economy. This data-driven framework may be of interest to stakeholders who support traditional area-based conservation models, but also to those who have been historically opposed to MPAs or have been excluded from past conservation processes.

Microalgae-bacteria consortia dynamics in a long term operated membrane-coupled high-rate algal pond (MHRAP) - Stéphanie Aparicio; Alejandro Ríos-Mejía; Juan Pablo Gallardo-Mejías; Ángel Robles; Luis Borrás (Journal of Environmental Management, 2024)

Interspecific relationships in a suboptimal habitat, an unexpected ally for the survival of the threatened Tenerife speckled lizard (Gallotia intermedia) - Gonzalo Albaladejo Robles; Alejandro Escánez; Alicia V Perera-Castro (European Journal of Wildlife Research, 2024)
Anthropogenic-driven environmental changes are pushing species to the limits of their habitats. More often species are restricted to relic or suboptimal habitats that present the minimum requirements to sustain species populations. In this scenario of accelerated environmental change and biodiversity loss, is fundamental to understand why species can survive in such suboptimal conditions. In this study, we show how the Tenerife speckled lizard ( Gallotia intermedia ), a critically endangered endemic reptile from the Canary Islands, can maintain stable populations in relic habitats thanks to its interactions with the yellow-legged gull ( Larus michahellis ) colony. A stable isotope analysis revealed that G. intermedia relies on marine subsidies for its diet and that the foraging area of this reptile is likely to be restricted to the limits of L. michahellis breeding colony. Furthermore, an antipredator behaviour analysis showed that L. michahellis displayed a strong anti-predator or mobbing response against cats, one of the main threats for G. intermedia , thus potentially providing some protection to the reptiles inhabiting the seabird colony. Our results show how unusual and poorly studied biotic interactions can provide valuable resources and conditions for the conservation of a critically endangered species inhabiting a suboptimal or relict habitat.

Unveiling potential PET degrading eukaryotes through in silico bioprospecting of PETases - Andrés Méndez-Zamora; Tania Diaz-Vidal; Marcela Robles-Machuca; Alejandro Pereira-Santana; Leticia Casas-Godoy (Science of The Total Environment, 2024)

Performance evaluation of Trichoderma reseei in tolerance and biodegradation of diuron herbicide in agar plate, liquid culture and solid-state fermentation - Alejandro Reyes-Cervantes; Diana Laura Robles-Morales; Edgar Noé Tec-Caamal; Angélica Jiménez-González; Sergio Alejandro Medina-Moreno (World Journal of Microbiology and Biotechnology, 2024)

Optimizing capacitance performance: Solar pyrolysis of lignocellulosic biomass for homogeneous porosity in carbon production - Diego Ramón Lobato-Peralta; Carlos Ernesto Arreola-Ramos; Alejandro Ayala-Cortés; Daniella Esperanza Pacheco-Catalán; Miguel Robles; Alfredo Guillén-López; Jesús Muñiz; Patrick U. Okoye; Heidi Isabel Villafán-Vidales; Camilo Alberto Arancibia-Bulnes; Ana Karina Cuentas-Gallegos (Journal of Cleaner Production, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Spent coffee grounds as feedstock for the production of biosurfactants and the improved recovery of melanoidins - Ignacio Moya-Ramírez; María Encarnación Pegalajar-Robles; Michele Debiasi Alberton; José A. Rufián-Henares; Alejandro Fernández-Arteaga; Miguel Garcia-Roman; Deisi Altmajer-Vaz (World Journal of Microbiology and Biotechnology, 2023)
Spent coffee grounds (SCG) are wastes generated in high amounts worldwide. Their composition makes them a promising feedstock for biotechnological processes. Here we show that the production of the biosurfactant surfactin by submerged culture of a Bacillus subtilis strain growing on SCG is possible, reaching concentrations up to 8.8 mg/L when using SCG at 8.3 g/L in the medium. In addition, we report a synergy between the production of surfactin and the recovery of melanoidins, an added-value compound already present in SCG. More specifically, the concentration of melanoidins in the culture medium increased between 2.1 and 2.5 times thanks to the presence of the B. subtilis in the culture. Furthermore, we have observed a strong interaction between surfactin and melanoidin aggregates through dynamic light scattering measurements, and that both of them can be co-purified with an acid precipitation. We have also characterized the interfacial and antioxidant properties of the cell-free supernatant and surfactin extract, as well as the distribution of the congeners of the biosurfactant. Altogether, this work describes a promising approach to obtain biosurfactants and antioxidant molecules in a single operation, which can be used to design several new formulations of interest for bioremediation, amendment of soils, food and cosmetics.

Environmental impact assessment of nanofluids containing mixtures of surfactants and silica nanoparticles - Manuela Lechuga; Mercedes Fernández-Serrano; Francisco Ríos; Alejandro Fernández-Arteaga; Ramón Jiménez-Robles (Environmental Science and Pollution Research, 2022)
Due to widespread use of nanoparticles in surfactant-based formulations, their release into the environment and wastewater is unavoidable and toxic for biota and/or wastewater treatment processes. Because of concerns over the environmental impacts of nanofluids, studies of the fate and environmental impacts, hazards, and toxicities of nanoparticles are beginning. However, interactions between nanoparticles and surfactants and the biodegradability of these mixtures have been little studied until now. In this work, the environmental impacts of nanofluids containing mixtures of surfactants and silica nanoparticles were valuated. The systems studied were hydrophilic silica nanoparticles (sizes 7 and 12 nm), a nonionic surfactant (alkyl polyglucoside), an anionic surfactant (ether carboxylic acid), and mixtures of them. The ultimate aerobic biodegradation and the interfacial and adsorption properties of surfactants, nanoparticles, and mixtures during biodegradation were also evaluated. Ultimate biodegradation was studied below and above the CMCs of the individual surfactants. The interfacial and adsorption properties of surfactant solutions containing nanoparticles were influenced by the addition of silica particles. It was determined that silica nanoparticles reduced the capability of the nonionic surfactant alkyl polyglucoside to decrease the surface tension. Thus, silica NPs promoted a considerable increase in the surfactant CMC, whereas the effect was opposite in the case of the anionic surfactant ether carboxylic acid. Increasing concentrations of surfactant and nanoparticles in the test medium caused decreases in the maximum levels of mineralization reached for both types of surfactants. The presence of silica nanoparticles in the medium reduced the biodegradability of binary mixtures containing nonionic and anionic surfactants, and this effect was more pronounced for larger nanoparticles. These results could be useful in modelling the behaviour of nanofluids in aquatic environments and in selecting appropriate nanofluids containing nanoparticles and surfactants with low environmental impact. Graphical abstract

Exclusive circulation of canine parvovirus type 2c in the Guadalajara metropolitan area in western Mexico: a five-year study - César Pedroza-Roldán; Martín Alejandro Hernández-Almaraz; Darwin Elizondo-Quiroga; Abel Gutierrez-Ortega; Carlos Maximiliano Acosta-Monroy; Claudia Charles-Niño; Mauricio Realpe-Quintero; Sandra Del Carmen Robles-Gil (Archives of Virology, 2022)

Stem Cell Therapy in the Treatment of Patients With Autism Spectrum Disorder: a Systematic Review and Meta-analysis - Laura Villarreal-Martínez; Gerardo González-Martínez; Melissa Sáenz-Flores; Andrea Judith Bautista-Gómez; Adrián González-Martínez; Miguel Ortiz-Castillo; David Alejandro Robles-Sáenz; Elizabeth Garza-López (Stem Cell Reviews and Reports, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Assessing seasonal and long-term mangrove canopy variations in Sinaloa, northwest Mexico, based on time series of enhanced vegetation index (EVI) data - César Alejandro Berlanga-Robles; Arturo Ruiz-Luna (Wetlands Ecology and Management, 2020)

Correction to: Comparing the Neuroprotective Effects of Caffeic Acid in Rat Cortical Slices and Caenorhabditis elegans: Involvement of Nrf2 and SKN-1 Signaling Pathways - Aline Colonnello; Gabriela Aguilera-Portillo; Leonardo C. Rubio-López; Benjamín Robles-Bañuelos; Edgar Rangel-López; Samaria Cortez-Núñez; Yadira Evaristo-Priego; Alejandro Silva-Palacios; Sonia Galván-Arzate; Rodolfo García-Contreras; Isaac Túnez; Pan Chen; et al. (Neurotoxicity Research, 2020)

Comparing the Neuroprotective Effects of Caffeic Acid in Rat Cortical Slices and Caenorhabditis elegans: Involvement of Nrf2 and SKN-1 Signaling Pathways - Aline Colonnello; Gabriela Aguilera-Portillo; Leonardo C. Rubio-López; Benjamín Robles-Bañuelos; Edgar Rangel-López; Samaria Cortez-Núñez; Yadira Evaristo-Priego; Alejandro Silva-Palacios; Sonia Galván-Arzate; Rodolfo García-Contreras; Isaac Túnez; Pan Chen; et al. (Neurotoxicity Research, 2020)

Spatio-temporal mangrove canopy variation (2001–2016) assessed using the MODIS enhanced vegetation index (EVI) - Marta Rocío Nepita-Villanueva; César Alejandro Berlanga-Robles; Arturo Ruiz-Luna; J. Héctor Morales Barcenas (Journal of Coastal Conservation, 2019)

Estimation of Seismic and Aseismic Deformation in Mexicali Valley, Baja California, Mexico, in the 2006–2009 Period, Using Precise Leveling, DInSAR, Geotechnical Instruments Data, and Modeling - Olga Sarychikhina; Ewa Glowacka; Braulio Robles; F. Alejandro Nava; Miguel Guzmán (Pure and Applied Geophysics, 2015)

Identification and molecular characterization of Orf virus in Argentina - Andrea Peralta; Carlos Robles; Agustín Martínez; Lucía Alvarez; Alejandro Valera; Gabriela Calamante; Guido A. König (Virus Genes, 2015)

Dynamic expression of the sodium-vitamin C co-transporters, SVCT1 and SVCT2, during perinatal kidney development - Francisco Nualart; Tamara Castro; Marcela Low; Juan Pablo Henríquez; Karina Oyarce; Pedro Cisternas; Andrea García; Alejandro J. Yáñez; Romina Bertinat; Viviana P. Montecinos; María Angeles García-Robles (Histochemistry and Cell Biology, 2013)

Breed differences in calving interval in the humid Mexican tropic - Aída Lorena Murillo Medina; Alejandro Córdova-Izquierdo; Ramón Soriano Robles; Germán David Mendoza Martínez; Héctor Castillo-Juárez (Tropical Animal Health and Production, 2009)

A novel ARH splice site mutation in a Mexican kindred with autosomal recessive hypercholesterolemia - Samuel Canizales-Quinteros; Carlos A. Aguilar-Salinas; Adriana Huertas-Vázquez; María L. Ordóñez-Sánchez; Maribel Rodríguez-Torres; José L. Venturas-Gallegos; Laura Riba; Salvador Ramírez-Jimenez; Rocío Salas-Montiel; Giovani Medina-Palacios; Ludivina Robles-Osorio; Angel Miliar-García; et al. (Human Genetics, 2005)